Treadmill exercise alleviates stress-induced impairment of social interaction through 5-hydroxytryptamine 1A receptor activation in rats - Kim, Tae-Woon (J Exerc Rehabil, 2015)
Brain-derived neurotrophic factor (BDNF) and its receptors tyrosine kinase B (trkB), and cyclic adenosine monophosphate response element binding protein (CREB) have been suggested as the neurobiological risk factors causing depressive disorder. Serotonin (5-hydroxytryptamine, 5-HT) plays an important role in the pathogenesis of depression. We in-vestigated the effect of treadmill exercise on social interaction in relation with BDNF and 5-HT expressions following stress in rats. Stress was induced by applying inescapable 0.2 mA electric foot shock to the rats for 7 days. The rats in the exercise groups were forced to run on a motorized treadmill for 30 min once a day for 4 weeks. Social interaction test and western blot for BDNF, TrkB, pCREB, and 5-HT1A in the hippocampus were performed. The results indicate that the spend time with unfamiliar partner was decreased by stress, in contrast, treadmill exercise increased the spending time in the stress-induced rats. Expressions of BDNF, TrkB, and pCREB were decreased by stress, in contrast, treadmill exercise enhanced expressions of BDNF, TrkB, and pCREB in the stress-induced rats. In addition, 5-HT1A receptor expression was de-creased by stress, in contrast, treadmill exercise enhanced 5-HT1A expression in the stress-induced rats. In the present study, treadmill exercise alleviated stress-induced social interaction impairment through enhancing hippocampal plasticity and serotonergic function in the hippocampus. These effects of treadmill exercise are achieved through 5-HT1A receptor activation.